2016
DOI: 10.5935/1806-0013.20160025
|View full text |Cite
|
Sign up to set email alerts
|

Pain prevalence on public servants: association with sedentary behavior and physical leisure activity

Abstract: BACKGROUND AND OBJECTIVES:From usual actions which reflect lifestyle of those working on administrative functions, there is the sedentary behavior. This study aimed at associating prevalence of pain to sedentary behavior and physical activity level of public servants. METHODS: Sample was made up of 156 public servants of both genders, mean age of 39.8±12.3 years, working for a federal university of the Northeastern region of Brazil, who have answered a questionnaire with variables related to pain, sedentary be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…The multinomial regression of the present results revealed that administrative technicians and teachers are more likely of being sedentary compared to students, despite the fact that administrative technicians were more classified as insufficiently active than the other groups. Corroborating these findings, Toscano et al 15 observed that approximately 65% of public servants were insufficiently active and with high level of sedentary behavior at work (88.5%), which was measured in relation to sitting time (> 3.5h / day). In addition, individuals aged 18-24 years and with higher schooling were classified as more active than individuals of all older age groups.…”
Section: Discussionmentioning
confidence: 90%
“…The multinomial regression of the present results revealed that administrative technicians and teachers are more likely of being sedentary compared to students, despite the fact that administrative technicians were more classified as insufficiently active than the other groups. Corroborating these findings, Toscano et al 15 observed that approximately 65% of public servants were insufficiently active and with high level of sedentary behavior at work (88.5%), which was measured in relation to sitting time (> 3.5h / day). In addition, individuals aged 18-24 years and with higher schooling were classified as more active than individuals of all older age groups.…”
Section: Discussionmentioning
confidence: 90%
“…No Brasil, padrão semelhante foi visto em estudo que mostrou a redução do consumo de alimentos saudáveis e da prática de atividade física durante a pandemia, comparando-o com o período anterior 28 . A associação deste fator com a automedicação pode ser explicada por um extenso período com pouco movimento corporal, devido ao maior tempo de permanência dentro de casa, quadro este que pode ser agravado em professores devido ao maior tempo na posição sentado, que pode levar a dores osteomusculares 30 , resolvidas pela automedicação.…”
Section: Discussionunclassified
“…contínua; alterações na microcirculação, produção de metabólitos tóxicos e esgotamento intramuscular dos substratos energéticos24 .No presente estudo foi identificado que o comportamento sedentário se associou de forma independente com a DME em todas as regiões investigadas. Estudo realizado com trabalhadores de uma universidade federal do Nordeste brasileiro apontou que os indivíduos que passavam mais de 2 horas por dia sentados em frente à TV e os que ficavam sentados mais de 3,5 horas por dia no trabalho, apresentaram maiores probabilidades de presença de dor, principalmente na região da coluna vertebral25 . Corroborando esses achados, o tempo total de uso de equipamentos eletrônicos apresentou-se como fator de risco para a presença de dor cervical e toracolombar entre estudantes de 14 a 19 anos da rede pública estadual do Recife; e de DME em acadêmicos da área da saúde no sul do Brasil 26,27 .…”
unclassified